Ibn ʿArabī (1165-1240) and Rūmī (1207-1273) on the Question of Evil: Discontinuities in Sufi Metaphysics - Koca, Özgür (Islam and Christian-Muslim relations, 2017)
This article compares and contrasts Ibn ʿArabī’s and Rūmī’s accounts of evil. Ibn ʿArabī explains the existence of evil as a consequence of both metaphysical necessity and God’s volitional act. Evil is the inevitable ‘shadow’ of existence implied by the Infinity of God, and God’s mercy existentiates the possibilities ‘hidden’ in the Infinite, allowing this metaphysical necessity to emerge. In contrast to Ibn ʿArabī’s necessitarian-cum-volitional theodicy, Rūmī presents an almost exclusively volitional theodicy. He traces the roots of evil to the Divine Will. To preserve God’s moral perfection, he frequently points to the positive compensating functions of the existence of evil in the world. Ibn ʿArabī’s theodicy enables him to accentuate the necessity of evil in order to save the act of will, and hence God’s perfection, from being directly related to the emergence of evil. Rūmī’s volitional theodicy, however, relates the Divine Will directly to evil, and subsequently attempts to preserve the purity of the Divine intention by accentuating all the positive compensations.